(untitled) - McPhee, John (New York, 1994)
Heirs of General Practice is a frieze of glimpses of young doctors with patients of every age―about a dozen physicians in all, who belong to the new medical specialty called family practice. They are people who have addressed themselves to a need for a unifying generalism in a world that has become greatly subdivided by specialization, physicians who work with the "unquantifiable idea that a doctor who treats your grandmother, your father, your niece, and your daughter will be more adroit in treating you"
Keywords: Family medicine,Bác sĩ (Thực tập tổng quát),Physicians (General practice),Bác sĩ gia đình; United States,Hoa Kỳ,United States,Hoa Kỳ